A Hybrid Approach by CEEMDAN-Improved PSO-LSTM Model for Network Traffic Prediction. (12th September 2022) - Shao, Bilin; Song, Dan; Bian, Genqing; Zhao, Yu
Abstract : As an important part of data management, network traffic evaluation and prediction can not only find network anomalies but also judge the future trends of the network. To predict network traffic more accurately, a novel hybrid model, integrating Complete Ensemble Empirical Mode Decomposition with Adaptive Noise (CEEMDAN) with long short-term memory neural network (LSTM) optimized by the improved particle swarm optimization (IPSO) algorithm, is established for network traffic prediction. Firstly, an LSTM prediction model for the real-time mutation and dependence of network traffic is constructed, and the IPSO is applied to optimize the hyperparameters. Then, CEEMDAN is introduced to decompose sequences of raw network traffic data into several different modal components containing different information to reduce the complexity of the network traffic sequence. Finally, the evaluation of the experiments shows the feasibility and effectiveness of the proposed method by comparing it with other deep neural architectures and regression models. The results show that the proposed model CEEMDAN-IPSO-LSTM produced a significantly superior performance with a reduction of the prediction error.